FUNGSI ADVOKAT DALAM MENYELESAIKAN SENGKETA DI LUAR PENGADILAN - Eman Sulaiman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
This article discusses the Function of Advocates in Resolving Disputes Outside the Court. From the results of the discussion, it can be understood that the function of advocates in the settlement of civil disputes through non-trial (non-adjudication) efforts is to defend interests or represent clients in real, to realize resolving disputes for which they are responsible without going through a process in court (adjudication). Advocates in carrying out good functions, it is necessary to increase formal education, especially for advocates who are still in the bachelor (S1), so that understanding of legal science is deeper, because the development of science, especially legal science is increasingly developing, so that if advocates do not take the initiative to develop their knowledge, it will be left behind because the experience of practice alone does not guarantee there is quality for an advocate. Practical experience is supported by higher formal education, so the quality of advocates is increasingly visible.